Pengaruh Tapas Acupressure Technique Terhadap Tingkat Kecemasan pada Pasien Hipertensi - Eka Gayatri, Putu Mitha; Sumirta, I Nengah; Ari Kresna Dewi, Ni Luh Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Hypertension not only has a physical impact but also affects the patient's psychological condition, one of them is anxiety. Efforts that can be do to reduce anxiety in hypertensive patients are by providing non-pharmacological therapy, namely Tapas Acupressure Technique. Tapas Acupressure Technique is a simple technique that can be done easily, and is free of charge. The aims of research to determine effect of Tapas Acupressure Technique to level anxiety hypertension patients. This research used method pre-experimental design with one group pre-post test. Sampling using non-probability with purposive sampling. The numbersamples was 19 subjects. Data analysis using Non Parametric Test with Wilcoxon Signed Rank Test. Measuring the level of anxiety using Hamilton Anxiety Rating Scale (HARS). The results showed before given Tapas Acupressure Technique most the subjek penelitiants experienced mild anxiety 13 people (68.4%) and moderate anxiety 6 people (31.6%). After the treatment, there was no anxiety 5 people (26.3%), 12 people mild anxiety (63.2%), and 2 people moderate anxiety (10.5%). Tapas Acupressure Technique has a significant effect on the anxiety level of hypertension patients with p-value = 0,000 alpha 0.05, that Tapas Acupressure Technique can reduce anxiety levels in hypertension patients.